2008
DOI: 10.1002/app.28760
|View full text |Cite
|
Sign up to set email alerts
|

Polyfluorene copolymer with a multiply blocked rotaxane architecture in the main chain: Synthesis and characterization

Abstract: To improve the physical properties of polymer materials, a novel copolymer with a multiply blocked rotaxane architecture in the main chain was synthesized through Suzuki dehalogenative polycondensation from a 2,7-dibromofluorene/c-cyclodextrin (c-CD) inclusion complex and 9,9-dioctylfluorene-2,7-trimethylene diborate in the presence of a tetrakis(triphenylphosphine)palladium (0) catalyst. As demonstrated by computational calculations, the dioctyl groups were large enough to prevent the dethreading of c-CD mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 33 publications
0
15
1
Order By: Relevance
“…The size of the granules depends strongly on the chemical nature of the polymer, temperature, the concentration of the polymer solution and the rotaxane architecture. [38] Although we have shown previously for other copolymers [18] that the formation of rotaxane architecture generally improves the morphological properties, this was not found to be the case for PF-PTÁCD, providing an interesting exception to the rule.…”
Section: Resultsmentioning
confidence: 42%
See 1 more Smart Citation
“…The size of the granules depends strongly on the chemical nature of the polymer, temperature, the concentration of the polymer solution and the rotaxane architecture. [38] Although we have shown previously for other copolymers [18] that the formation of rotaxane architecture generally improves the morphological properties, this was not found to be the case for PF-PTÁCD, providing an interesting exception to the rule.…”
Section: Resultsmentioning
confidence: 42%
“…In addition, the macrocycles can improve the solubility via host-induced guest solubilization and modify the photophysical properties due to its confinement effects. Not surprisingly, numerous studies have been done to understand the influence of rotaxane and pseudorotaxane formation on the electro-optical properties of different threaded conjugated polymers, [17][18][19][20][21][22][23][24][25] but the design and synthesis of such rotaxane or pseudorotaxane architectures has remained a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…The construction of mechanically interlocked molecules, such as rotaxanes and polyrotaxanes, was also investigated as a method of further improvement of electronic properties through insulating the backbones of conjugated polymers for controlling intermolecular interactions 22–31. These studies revealed an attractive approach to achieve higher degree of control over molecular rigidity, prevention of aggregation, fluorescence efficiency, improved solubility, and surface‐morphological properties of the resulting conjugated polyrotaxanes 24–31…”
Section: Introductionmentioning
confidence: 99%
“…The reaction can be performed under mild experimental conditions using a copper (I) catalyst 8–12. This reaction has found a vast number of applications in different research fields, such as material sciences,11, 12 polymer chemistry,13–21 and pharmaceutical sciences 5, 6, 13–16…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] This reaction has found a vast number of applications in different research fields, such as material sciences, 11,12 polymer chemistry, [13][14][15][16][17][18][19][20][21] and pharmaceutical sciences. 5,6,[13][14][15][16] It has been extensively used in the synthesis of polymers with different composition and topology. 8 In spite of the importance of polyimides (PI), click chemistry has not been widely employed for the preparation of these compounds.…”
Section: Introductionmentioning
confidence: 99%